2019
DOI: 10.1088/2053-1591/ab4df2
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state ferrimagnetism and magneto-caloric effects in Nd2NiMnO6

Abstract: Extending our earlier investigation of magnetic properties of Nd2NiMnO6, we show that it exhibits a magnetic transition below ∼6 K to a ferrimagnetic state. This behavior is interpreted as arising from a long-range ordering of Nd moments antiferromagnetically coupled to the ferromagnetic Ni–Mn ordered moments. Due to the richness of its multiple magnetic transitions and the easily influenced magnetic state by the application of an external magnetic field, established in our earlier study, it has a remarkable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The experimental study 27 on CaMnReCoO reports only magnetic susceptibility, and do not report dM/dT. However reported experimental dM/dT data for multiple magnetic ion containing Nd NiMnO double perovskite does exhibit such peak-shoulder structure 37 . Such two feature dM/dT curve is also seen for ferrimagnetic compound NiCr O 38 .…”
Section: Resultsmentioning
confidence: 97%
“…The experimental study 27 on CaMnReCoO reports only magnetic susceptibility, and do not report dM/dT. However reported experimental dM/dT data for multiple magnetic ion containing Nd NiMnO double perovskite does exhibit such peak-shoulder structure 37 . Such two feature dM/dT curve is also seen for ferrimagnetic compound NiCr O 38 .…”
Section: Resultsmentioning
confidence: 97%
“…However reported experimental dM/dT data for multiple magnetic ion containing Nd 2 NiMnO 6 double perovskite does exhibit such two feature structure. [34] Such two feature dM/dT curve is also seen for ferrimagnetic compound NiCr 2 O 4 . [35] We notice with choice of DFT estimated value of D M n1−Co , the second feature appears around 200 K, very close to experimentally reported T C of 188 K. [27] Effect of Off-stoichiometry…”
Section: Monte Carlo Study Of the Spin Hamiltonianmentioning
confidence: 66%
“…7(a)-(c) (Fig. 7(d)-(f)) 32 . In case of antialignment, external magnetic field can enforce an alignment and hence ∆S M also shows a sign reversal at sufficiently large magnetic field (see, for example, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Taken at face value the above observations seem to indicate that there is antiferromagnetic coupling between the R and Ni-Mn sublattice for R = Pr, Nd, and Sm, while this coupling is ferromagnetic for R = Gd, Tb, and Dy. [30][31][32] . However, recent DFT calculations of the exchange constants in Nd 2 NiMnO 6 have shown that the magnetic exchange between the Nd spin and the Ni-Mn sublattice is ferromagnetic ?…”
Section: Resultsmentioning
confidence: 99%